PENTINGNYA LAYANAN INFORMASI DALAM MENINGKATKAN PEMAHAMAN MENGENAI KESEHATAN MENTAL PADA REMAJA - Melisa Chandra; Nadjwa Khairunnisa; Haliza Nurika; Siti Yolandari (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2024)
Understanding mental health in adolescents has an important role in increasing awareness of the importance of maintaining psychological well-being. Information services have a significant role in providing adolescents with accurate and relevant information about mental health. The research method used in this research is literature study which is a qualitative method. The research results show that information services play an important role in educating teenagers about mental health. There are several factors that cause teenagers to experience mental health which can be overcome by providing education and assistance to teenagers who experience mental health. By providing appropriate education, information services help young people understand the signs of mental disorders, risk factors, and actions they can take to maintain their mental health.